Improving the spatial‐temporal analysis of Amazonian fires - Berenguer, Erika; Carvalho, Nathália; Anderson, Liana O.; Aragão, Luiz E. O. C.; França, Filipe; Barlow, Jos (Global change biology, 2021)
There is a growing interest in Amazonian fires, accompanied by a substantial increase in research in the subject. Here, we list five common misunderstandings about Amazonian climate, vegetation, fires and the deforestation process to help to support future research.